A comparative 18F-FDG and an anti-PD-L1 probe PET/CT imaging of implant-associated Staphylococcus aureus osteomyelitis - Ren, Shu-Qi; Ma, Yuan; Fu, Li-Lan; Hu, Kong-Zhen; Liang, Hao-Ran; Yu, Bin; Tang, Gang-Hua (Frontiers in Cellular and Infection Microbiology, 2023)
Early and accurate diagnosis of osteomyelitis can improve treatment outcomes. Osteomyelitis caused by infection often leads to increased PD-L1 expression. Nuclear imaging using radiolabeled anti-PD-L1 allows for sensitive and quantitative assessments of PD-L1 expression on a whole-body scale, without invasive procedures. Therefore, we synthesized an anti-PD-L1 probe to detect osteomyelitis lesions early and accurately. This study compared 18F-FDG and an 18F-labeled PD-L1-Binding Peptide probe (18F-PD-L1P) in PET imaging of Implant-Associated Staphylococcus aureus Osteomyelitis (IAOM). Compared with 18F-FDG, 18F-PDL1P demonstrated higher ％ID/g ratios (i.e., radioactivity ratios between the infected and non-infected sides) for both post-infected 7-day tibias (P=0.001) and post-infected 21 days (P=0.028). The intensity of 18F-PD-L1P uptake reflected the pathological changes of osteomyelitic bones, which were measured by PD-L1 Immunohistochemistry (IHC). Compared to 18F-FDG, 18F-PDL1P provides earlier and more sensitive detection of osteomyelitis caused by S. aureus.